The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/mnras/stab2499
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Fermi GRB optical counterparts with the prototype Gravitational-wave Optical Transient Observer (GOTO)

Abstract: The typical detection rate of ∼1 gamma-ray burst (GRB) per day by the Fermi Gamma-ray Burst Monitor (GBM) provides a valuable opportunity to further our understanding of GRB physics. However, the large uncertainty of the Fermi localization typically prevents rapid identification of multi-wavelength counterparts. We report the follow-up of 93 Fermi GRBs with the Gravitational-wave Optical Transient Observer (GOTO) prototype on La Palma. We selected 53 events (based on favourable observing conditions) for detail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…For gamma-ray transients, it is essential to provide a localization for every GRB detected to enable multiwavelength/multimessenger follow-up. The localization informs telescopes where on the sky to observe to find a coincident counterpart [2,4,11] and provides information on whether two independent observations of a transient signal are associated. If a coincident counterpart is detected, the localization can be used to improve the localization even further.…”
Section: Pos(icrc2023)953mentioning
confidence: 99%
“…For gamma-ray transients, it is essential to provide a localization for every GRB detected to enable multiwavelength/multimessenger follow-up. The localization informs telescopes where on the sky to observe to find a coincident counterpart [2,4,11] and provides information on whether two independent observations of a transient signal are associated. If a coincident counterpart is detected, the localization can be used to improve the localization even further.…”
Section: Pos(icrc2023)953mentioning
confidence: 99%
“…sGRB detection rates range between 10 and 40 per year for the GRB instruments on board the Neil Gehrels Swift Observatory (Gehrels et al 2004) and the Fermi satellite respectively (Abdo et al 2008). However, the optical counterparts for these bursts have proven to be elusive, mainly because the localization of Fermi sGRBs typically spans hundreds of square degrees (e.g., Mong et al 2021;Ahumada et al 2022). The follow-up of BNS and neutron star-black hole (NSBH) mergers detected by the International Gravitational-Wave Network, consisting of Advanced LIGO, Advanced Virgo, and KAGRA (LVK), during the third observing run (O3) has not been fruitful, possibly due to the fact that the GW sky maps are similarly large (Andreoni et al 2019(Andreoni et al , 2020aGoldstein et al 2019;Gompertz et al 2020;Kasliwal et al 2020;Chang et al 2021;Petrov et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Singer et al 2013(Singer et al , 2015 have successfully found optical counterparts to GBM LGRBs using the intermediate Palomar Transient Factory (iIPTF) (Law et al 2009;Rau et al 2009), and other have serendipitously found orphan afterglows and LGRBs using ZTF (Andreoni et al 2021;Ho et al 2022). There are ongoing projects like Global MASTER-Net (Lipunov et al 2005), and the Gravitational-Wave Optical Transient Observe (GOTO; Mong et al 2021) that are using optical telescopes to scan the large regions derived by GBM. We note that the optical afterglows of LGRBs are usually brighter than those of SGRBs, thus the ToO strategy might differ from the one presented in this paper.…”
Section: Introductionmentioning
confidence: 99%